Analisis Kepuasan Pelanggan Pada Perusahaan Daerah Air Minum Tirta Nusa Kabupaten Natuna - Samsudin A; Ayu Andira (Universitas Muhammadiyah Pontianak, 2015)
This study analyzes customer satisfaction provided by PDAM Tirta Nusa Natuna. The customer satisfaction survey was conducted to determine customer satisfaction is of the data obtained through interviews, observation, and questionnaire. Data were analyzed using Cartesian diagram. The sample of 100 clients drawn from a population of 3,161 customers in 2013. The results showed that the respondents were dissatisfied with the services provided by PDAM.This can be seen in a comparison of the satisfaction and expectations of respondents. The average score of satisfaction was 3.17 and the average score of importance was 4.39.